Neonatal admission after lithium use in pregnant women with bipolar disorders: a retrospective cohort study - Noralie N. Schonewille; Pleun A. Terpstra; Maria E. N. van den Heuvel; Maria G. Van Pampus; Odile A. van den Heuvel; Birit F. P. Broekman (International Journal of Bipolar Disorders, 2023)
Abstract Background Lithium is the preferred treatment for pregnant women with bipolar disorders (BD), as it is most effective in preventing postpartum relapse. Although it has been prescribed during pregnancy for decades, the safety for neonates and obstetric outcomes are a topic of ongoing scientific debate as previous research has yielded contradicting outcomes. Our study aims to compare (re)admission rates and reasons for admissions in neonates born to women with bipolar disorders (BD) with and without lithium exposure. Methods A retrospective observational cohort study was conducted in a Dutch secondary hospital (two locations in Amsterdam). Women with BD who gave birth after a singleton pregnancy between January 2011 and March 2021 and their neonates were included. Outcomes were obtained by medical chart review of mothers and neonates and compared between neonates with and without lithium exposure. The primary outcome was admission to a neonatal ward with monitoring, preterm birth, small for gestational age (SGA), 5-minute Apgar scores, neonatal asphyxia, and readmission ≤ 28 days. Results We included 93 women with BD, who gave birth to 117 live-born neonates: 42 (36%) exposed and 75 (64%) non-exposed to lithium. There were no significant differences in neonatal admission with monitoring (16.7 vs. 20.0%, p = 0.844). Additionally, preterm birth (7.1 vs. 5.3%), SGA (0.0 vs. 8.0%), 5-minute Apgar scores (means 9.50 vs. 9.51), neonatal asphyxia (4.8 vs. 2.7%) and readmission (4.8 vs. 5.3%) were comparable. Overall, 18.8% of BD offspring was admitted. Women with BD had high rates of caesarean section (﻿29.1%), gestational diabetes (12.8%) and hypertensive disorders of pregnancy (8.5%). Conclusions In a sample of neonates all born to women with BD using various other psychotropic drugs, exposure to lithium was not associated with greater risk of neonatal admission to a ward with monitoring compared to non-exposure to lithium, questioning the necessity for special measures after lithium exposure. However, offspring of women with BD was admitted regularly and women with BD have high obstetric risk which require clinical and scientific attention.